Validation of the survival model including cardiac substructure dosimetry in NSCLC - Vivekanandan, S; Panakis, N; Higgins, G; Stuart, R; Landau, D; Cooke, R; Chu, K; Fresen, J; Fenwick, J; Hawkins, M (Elsevier, 2018)
In lung cancer radiotherapy (RT) high doses are delivered to the heart. We found significant associations between death rate (DR) and high left atrial wall (LAWall) volumes receiving 63-69Gy (LAWallV63-69) and any new or worsening ischaemic or rhythm ECG changes within 6 months of RT in a prospective isotoxic dose-escalation trial of 78 locally advanced non-small cell lung cancer (LA-NSCLC) patients. Here we aim to validate these findings in an independent retrospective cohort.